Injuries of primary school children during sports activities - Videmšek, Mateja (Zdravstveno varstvo, 2023)
Introduction: The purpose of the research was to analyse the injuries of primary school children in the framework of organised sports activities at school and in clubs or associations, and in leisure time without professional guidance. Methods: We surveyed 631 participants, of which there were 282 boys and 349 girls from eight Slovenian primary schools. Frequencies were calculated and a Chi-square test was performed. Results: In physical education (PE) at school, 32% of the participants were injured in one school year, and there were no statistically significant differences in the number of injuries according to sex (p=0.18) and age (p=0.12). Most injuries were recorded in the lower extremities (50%), in the form of wounds. The participants were injured less often in PE at school than in a club or association, and more often than in their leisure time. The participants were absent from PE classes for longer after an injury in a club or association than in PE, while no significant differences in absences after injury were found. At school, the participants were most often injured in ball games, boys in football (43%) and girls in volleyball (19%). In activities in a club or association, we recorded the most injuries in boys in martial arts (18%) and dance for girls (19%). In their leisure time, boys suffered the most injuries from football (26%) and cycling, while girls suffered the most from running and rollerblading. Conclusion: In the last ten years, the number of injuries in PE has increased in Slovenia. Based on the obtained results, we propose measures to reduce injuries and thus encourage more sports activities among children and adolescents, while ensuring their safety.
Keywords: children; injuries; leisure time; osnovne šole; otroci; physical education; poškodbe; primary schools; prosti čas; športna vzgoja